2021
DOI: 10.1186/s12911-021-01609-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a smartphone application on women’s performance and health beliefs about breast self-examination: a quasi-experimental study

Abstract: Background Breast Self-Examination (BSE) is a simple and inexpensive method for early diagnosis of breast cancer. This study aimed to determine the effect of a smartphone application on women’s performance and health beliefs regarding BSE. Methods In this quasi-experimental study, 150 women referring to therapeutic clinics in Jahrom, Iran from December 2019 to May 2020 were randomly assigned to an intervention or a control group. The intervention g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 28 publications
1
17
0
4
Order By: Relevance
“…This study highlights the importance of mobile apps based on how people's health and well-being can be improved via monitoring ( 15 ). This result matches those observed in a study in Iran that implemented the smartphone app, which improved BSE practice and even reported abnormal findings among participants by mass palpation or visually inspected nipple retraction ( 16 ). According to the Health Belief Model (HBM), an individual's opinion that she is vulnerable to BC, the severity of BC, and the benefits, as well as a barrier to preventative action such as doing the BSE and screening at the hospital, all influence health-seeking behavior toward BC prevention ( 6 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study highlights the importance of mobile apps based on how people's health and well-being can be improved via monitoring ( 15 ). This result matches those observed in a study in Iran that implemented the smartphone app, which improved BSE practice and even reported abnormal findings among participants by mass palpation or visually inspected nipple retraction ( 16 ). According to the Health Belief Model (HBM), an individual's opinion that she is vulnerable to BC, the severity of BC, and the benefits, as well as a barrier to preventative action such as doing the BSE and screening at the hospital, all influence health-seeking behavior toward BC prevention ( 6 ).…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, another study promotes the app's credibility by enabling direct communication with the therapist ( 16 ). Furthermore, the reminder feature notifications as cues in the app improve user engagement and BSE routine in a time duration set according to the user's menstrual cycle ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…They came to the conclusion that the telephone-delivered intervention was effective in engaging patients in care and improving their disabilities [ 38 ]. Another study also revealed that having access to smartphone apps enhanced women’s performance, self-efficacy, and health beliefs in breast self-examination [ 39 ]. Evidence has shown that during the COVID-19 outbreak, smartphones and apps have played a key role in several aspects of healthcare delivery and clinical practice among healthcare professionals [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has demonstrated that older women handle these hurdles depending on their social and cultural backgrounds. In other words, each disease is caused, experienced, and managed differently by different people based on the social and cultural backgrounds of the society they live in van den Muijsenbergh and Lagro-Janssen (2006) , Andersson et al (2008) , Hayder and Schnepp (2010) , Gjerde (2012) , Shirazi et al (2014) , Özkan et al (2015) , Heidari et al (2021) , Shakery et al (2021) . Thus, to determine the psychosocial effects of urinary incontinence on older women, their sociocultural backgrounds should be considered ( Sinclair and Ramsay, 2011 ; Laganà et al, 2014 ; Alshammari et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%